The Nature Terrorism Reports on Social Networks - James Okolie-Osemene; Rosemary Ifeanyi Okoh (Glocalism: Journal of Culture, Politics and Innovation)
As new tools of communication, an in-depth study of social networking in the era of global terrorism is attempted in this article. This emerging tradition of information sharing is driven by social media technology which has greatly revolutionalised communication in all sectors. The article explored the information sharing relevance of new technologies in the age of terrorism and counterterrorism. It focused on how social networks are increasingly utilised by different groups. In terms of methodology, the study extracted and utilised positive, negative and neutral posts, updates, tweets and reports on social networks through different individual and organisational media accounts and blogs, and analysed the data qualitatively. Findings show that despite being used by extremist groups in promoting their political agenda, social networks are also useful in promoting positive perceptions that society has about Muslims in the era of terrorism, emphasising that Muslims are not terrorists. Through the instrumentality of social media, users are able to map the trends of terrorism and responses from stakeholders in government and security sector in curbing the menace. Given their capacity to reach a wider audience, breaking cultural and religious barriers, social networks serve as early warning signs and make it possible for people to share new ideas on possible ways of curbing the proliferation of terrorist organisations.